2015
DOI: 10.1111/trf.13038
|View full text |Cite
|
Sign up to set email alerts
|

A randomized noninferiority crossover trial of corrected count increments and bleeding in thrombocytopenic hematology patients receiving 2‐ to 5‐ versus 6‐ or 7‐day–stored platelets

Abstract: BACKGROUND: Bacterial screening offers the possibility of extending platelet (PLT) storage to Day 7. We conducted a noninferiority, crossover trial comparing PLTs stored for 6 or 7 days versus 2 to 5 days. STUDY DESIGN AND METHODS: Stable hematology patients were allocated to receive blocks of 2-to 5-and 6-or 7-day PLTs in random order. The primary outcome was the proportion of successful transfusions during the first block, defined as a corrected count increment (CCI) of more than 4.5 at 8 to 24 hours posttra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 27 publications
(31 reference statements)
4
41
1
Order By: Relevance
“…In line with literature, TEG measurements did not correlate with storage time, suggesting that this test is unable to monitor development of PSL and concomitant effects on 1‐hour CCIs. However, as CCI is a poor predictor of bleeding tendency, investigating the correlation between bleeding and product quality using TEG remains of interest.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In line with literature, TEG measurements did not correlate with storage time, suggesting that this test is unable to monitor development of PSL and concomitant effects on 1‐hour CCIs. However, as CCI is a poor predictor of bleeding tendency, investigating the correlation between bleeding and product quality using TEG remains of interest.…”
Section: Discussionmentioning
confidence: 68%
“…The effectiveness of these prophylactic transfusions is usually monitored with the 1‐ and/or 24‐hour corrected count increment (CCI), which is the increase in circulating PLTs corrected for the administered dose and the blood volume of the patient. Despite being a poor surrogate marker for bleeding tendency, CCIs are associated with the time to next transfusions 5 and are therefore of clinical relevance.…”
mentioning
confidence: 99%
“…We used platelets that were past their 5‐day clinical expiry date but less than 7 days old. Platelet concentrates are stored for only 5 days in the United States to limit bacterial overgrowth, but trials in humans show no difference in other laboratory or clinical outcomes between 5‐ and 7‐day platelets . Although platelets are stored at 22°C, ongoing trials of cold‐stored platelets may lead to a change in practice and increased risk of hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently two published meta‐analyses showed that storage time plays an important role in the balance between efficacy, safety, and costs . Time to the next transfusion, as an outcome, was found to be reported in eight reviewed papers . Four of these studies could be meta‐analyzed and the interval between PLT transfusions after transfusion of old PLTs estimated to be 0.25 days (95% confidence interval [CI], 0.13‐0.38 days) shorter compared to transfusion of fresh PLTs …”
mentioning
confidence: 99%
“…3,4 Time to the next transfusion, as an outcome, was found to be reported in eight reviewed papers. [5][6][7][8][9][10][11][12] Four of these studies could be meta-analyzed and the interval between PLT transfusions after transfusion of old PLTs estimated to be 0.25 days (95% confidence interval [CI], 0.13-0.38 days) shorter compared to transfusion of fresh PLTs. 3,[5][6][7][8] The influence of storage time on PLT recovery and survival could be affected by the type of PLT component transfused.…”
mentioning
confidence: 99%